Crown Ether‐Based Supramolecular Polymers: From Synthesis to Self‐Assembly - Duan, Zhaozhao; Xu, Fenfen; Huang, Xiaohui; Qian, Yongchao; Li, Hui; Tian, Wei (Macromolecular rapid communications., 2022)
Supramolecular polymers not only possess many advantages of traditional polymers, but also have many unique characteristics. Supramolecular polymers can be constructed by self‐assembly of various noncovalent interactions. Host–guest interaction, as one important type of noncovalent interactions, has been widely applied to construct supramolecular polymers. From the perspective of classification of the recognition system motifs, host–guest recognition motifs mainly include crown ether, cyclodextrin, calixarene, cucurbituril, and pillararene‐based host–guest recognition pairs. Crown ethers, as the first‐generation macrocyclic hosts, have played a very important part in the development of supramolecular chemistry. Due to the easy modification of crown ethers, various crown ether derivatives have been prepared by attaching some functional groups to the edges of crown ethers, which endowed them with some interesting properties and made them ideal candidates for the fabrication of supramolecular polymers. This review gives a review of the preparation of crown ether‐based supramolecular polymers (CSPs) and summarizes crown ether‐based recognition pairs, organization methods, topological structures, stimuli‐responsiveness, and functional characteristics. Crown ether‐based supramolecular polymers (CSPs) not only possess many merits of traditional covalent polymers but also endow many unique properties. This review article gives an overview of the preparation of CSPs and covers recent research advance and future trends of crown ether‐based host–guest pairs, assembly methods, topological architectures, stimuli‐responsiveness, and functional features.